Signifikansi Pengaturan Strict Liability dalam Peraturan Mahkamah Agung No. 1 Tahun 2023 tentang Pedoman Mengadili Perkara Lingkungan Hidup untuk Mengatasi Kerancuan Konseptualnya dalam Praktik - Muhamad Agil Aufa Afinnas (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Before the enactment of Supreme Court Regulation (PERMA) No.1/2023, there was conceptual confusion regarding the application of strict liability in civil environmental cases. Firstly, misconceptions were indicated in the practice that required the plaintiff to prove that the defendant had committed an unlawful act (PMH). Secondly, there was an interpretation equating strict liability with shifting the burden of proof concerning fault elements. This research aims to analyze the significance of PERMA No.1/2023 in addressing these misconceptions. This is a doctrinal legal research. The findings indicate that PERMA No.1/2023 has provided normative guidelines and clarity, particularly for judges, in handling civil environmental cases that involve strict liability. Article 38 paragraph (3) of PERMA No.1/2023, which specifies what needs to be proven by the plaintiff when invoking strict liability as a basis for liability, addresses the first misconception. In this context, it is clear that the element of fault/unlawful act is irrelevant under strict liability. Meanwhile, Article 40 paragraph (1) of the PERMA emphasizes that strict liability is distinct from shifting the burden of proof concerning fault elements.